THE CALCULATION OF THE EFFICIENCY OF THE PERSONNEL ELEMENT OF THE POTENTIAL INTANGIBLE ASSETS OF INDUSTRIAL ENTERPRISES - I. Buzurnaya (Вестник университета)
In the article the analysis of features of calculation of index of potential intangible assets of the industrial enterprise as linear combinations of the quantitative values of each object of potential intangible assets and their weights.